Reduction of Escherichia coli Contamination in Vannameii Shrimp (Litopenaeus vannamei) using Cassava Leaf Extract (Manihot glaziovii) and Noni Fruit (Morinda citrifolia L.) - Vina Asfia Chori; Dewi Sartika; Sri Hidayati; Suharyono A. S.; Tanto P. Utomo (The University of Lampung, 2023)
This research is study of inhibition power between rubber cassava leaves extract (Manihot glaziovii) and noni (Morinda citrifolia l.) in reducing Eschericia coli contamination in vannameii shrimps (Litopenaeus vannamei). Cassava leaves contains flavonoids, saponins and tannins while noni contains antraquinone and scolopetin which has antimicrobial activity. This research aim at determine antimicrobial activity of cassava leaves extract and noni to inhibit Eschericia coli contamination in vannamei shrimps and determine the best formulation. The research use non-factorial complete randomized block design (RAKL) experimental design with three replications. The formulation in each treatment being used contained 25% (b/v) of the solvent. The treatments used in this study were M0S0 (control), M1S1 (25: 0), M2S2 (20: 5), M3S3 (15:10), M4S4 (10:15), M5S5 (5: 20), M6S6 (0:25) .Data were tested with the Barlett test and the Tuckey test to see the homogeneity. The data analysis was carried out using fingerprints to see the effect of treatment on the parameters being observed and followed with LSD test. The observations of research contained test of amount Eschericia Coli, Antimicrobial Inhibition, Eschericia coli Total Decrease, Antimicrobial Activity Application, pH test, and Sensory Testing (Color and Appearance). The results of this research showed that the extract of noni was more effective in inhibiting the contamination of Escherichia coli in vannamei shrimps with an inhibition zone of 7.23 mm compared to cassava leaves with an inhibition zone of 0.43 mm. The formulation has been obtained that the ratio between extracts of rubber cassava leaves and noni was 25%: 0% is best formulation to inhibit the microbial activity zwith the zone of inhibition is 7.23 mm. Keywords: Vannameii Shrimps, Rubber Cassava Leaves, Noni, Escherichia coli